SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL DARI LIMBAH KAYU Acacia crassicarpa PADA BEBERAPA UKURAN PARTIKEL DAN KONSENTRASI UREA FORMALDEHIDA - Aminah, .; Setyawati, Dina; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
This research aims to determine the effect of particle size and urea formaldehyde adhesive concentration on the physical and mechanical properties of particle board from Acacia crassicarpa wood waste, and to determine the particle size and concentration of the best urea formaldehyde to meet Â JIS A 5908-2003 standard. The materials used in this study are wood waste Acacia crassicarpa, urea formaldehyde adhesive, liquid paraffin and catalyst. The particle size used consisted of passing 4 mesh retained 6 mesh (coarse particles), passing 6 mesh retained 8 mesh (medium particle) and passing 8 mesh retained 10 mesh (fine particles), wereas the concentration of urea formaldehyde adhesive comprises 8%, 10% and 12%. The particle board is made with size 30 cm x 30 cm x 1 cm with target density of 0.70 gr/cm3 at pressure of 25 kg/cm2 and temperature of 120oC for 10 minutes. The results showed that particle size factor had a significant effect on density, moisture content, water absorption, internal bond strength and screw holding power, thickness swelling and MOR. The concentration factor of urea formaldehyde adhesive has significant effect on density, moisture content, thickness swelling, water absorption, MOE, MOR, internal bond strength and screw holding power. The interaction of both factors had a significant effect on moisture content and screw holding power. The best particle board in the recent study was on a particle board made of coarse particle size (passing 4 mesh retained 6 mesh) with a 12% urea formaldehyde adhesive concentration, in which the physical and mechanical properties of the particle board that meet JIS A 5908-2003 standard except for the thickness swelling.Keywords: adhesive concentration, particle board, particle size, physical and mechanical Â properties, wood waste Acacia crassicarpa